1997
DOI: 10.1159/000201508
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Hypertrophic Pyloric Stenosis and Achalasia: NO-Related or Non-Related Conditions?

Abstract: Background: The regulated ability of sphincters to relax allows adequate control of digestive transit. Relaxation of the lower esophageal sphincter (LES) is essential for esophageal emptying and, similarly, pyloric relaxation permits gastric emptying. When the relaxatory response of these sphincters is impaired, luminal transit is altered, as occurs in achalasia and hypertrophic pyloric stenosis. Nitric oxide (NO) has been identified as the main inhibitory neurotransmitter in both sphincteric regions. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Pyloric achalasia may be an appropriate terminology for this condition because there are few reports describing association of pyloric obstruction with and without muscular hypertrophy and esophageal achalasia in adolescents [3][4][5]. A thickened circular layer of muscularis propria forms the pyloric sphincter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyloric achalasia may be an appropriate terminology for this condition because there are few reports describing association of pyloric obstruction with and without muscular hypertrophy and esophageal achalasia in adolescents [3][4][5]. A thickened circular layer of muscularis propria forms the pyloric sphincter.…”
Section: Discussionmentioning
confidence: 99%
“…High-amplitude contractions in gastroduodenal junction uncoordinated with antral contractions are partially responsible for pylorospasm leading to IHPS [9][10][11]. Nitric oxide synthase deficiency leading to lack of locally available nitric oxide may cause failure of muscular relaxation and neuromuscular incoordination at pylorus [4,6,12]. Tack et al [13] have recently suggested that postinfectious dyspepsia, early satiety, weight loss, and vomiting are caused by dysfunction at the level of nitrergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to achalasia and Hirschprung's disease 52,53 which are also characterized by functional obstruction from failure of relaxation. Intriguingly, IHPS and achalasia has been reported in the same patient 54 . These findings have to be tempered with the knowledge that networks of interstitial cells of Cajal continue to develop postnatally; 55 this in part may account for the good prognosis of patients with IPHS following appropriate treatment.…”
Section: Clinical Disorders Of the Pylorusmentioning
confidence: 96%
“…These include HSCR (MIM 142623) (including one report of two affected male siblings) (Kelly et al 1997;Kohler et al 2005), duplication of the pylorus (Gupta and Hollander 1977;Jorge and Diaz 1976), additional achalasia of the pylorus (Kalsbeek and Voortman 1980), hypertrophic pyloric stenosis (MIM 179000) (Castro et al 1997;Cataliotti et al 2002), esophageo-rectal syndrome (Shafik 2003), megacystis-microcolon-intestinal hypoperistalsis syndrome (MIM 249210) (Al Harbi et al 1999), and situs inversus viscerum (MIM 270100) (Spinelli et al 1991). …”
Section: Other Syndromes and Diseasesmentioning
confidence: 99%